Large-scale transition of economic systems: Do CEECs converge towards western prototypes? - Markus Ahlborn; Joachim Ahrens; Rainer Schweickert (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
In order to identify convergence patterns among the group of Central and Eastern European Countries (CEECs) we analyze clusters of traditional OECD countries, i.e. EU-15 plus Norway and Switzerland, Anglo-Saxon non-EU countries plus Japan, and CEECs based on macro data on government regulation and spending instead of micro data on firm relations and market characteristics as is usually applied in Varieties-of-Capitalism (VoC) analysis. This framework is supposed to incorporate some of the critique that has been expressed towards the traditional VoCapproach, especially its ignorance of government spending and performance. We acknowledge for the transition aspect by looking at cluster history and principal component analysis for periods of transition. Our analysis reveals that there is consolidation rather than convergence with CEECs being divided in clusters leaning towards CME and LME prototypes respectively. Overall, there are worlds of redistribution within which clusters differ with respect to their mix of - negatively correlated - regulation and innovation. Interestingly, CEECs do not mix up with Mediterranean MMEs, which indeed provide a kind of worst case setting, while Scandinavian CMEs as well as traditional LMEs provide a kind of role model within their respective worlds of redistribution.
Keywords: H10; P10; P51; 330; varieties of capitalism; worlds of welfare states; government spending; regulation; cluster analysis; transition; economic systems; CEECs